Living Hadis PENERAPAN FAMMI BISYAUQIN DI PONDOK PESANTREN HAMALATUL QUR’AN PUTRI JOGOROTO: KAJIAN LIVING HADITS - Alyssa Qothrunnada; Amrulloh Amrulloh (Yayasan Haiah Nusratul Islam, 2025)
This study discusses the Fammi Bisyauqin tradition at the Hamalatul Qur'an Putri Jogoroto Islamic Boarding School in Jombang as a means of implementing Living Hadith in Al-Qur'an education. Fammi Bisyauqin is a method of reciting and memorizing the Al-Qur'an that is rooted in the practices of the salaf scholars and has a basis in hadith about the importance of maintaining memorization so that it is not easily lost. Unlike previous studies that emphasized the technical effectiveness of this method, this study highlights the hadith dimension and the social construction behind it. Using a qualitative approach with a Living Hadith perspective, this study combines Hadith and ethnography to explore the experiences of students, the process of meaning transmission, and religious symbols in the implementation of this tradition. Data was collected through participant observation, in-depth interviews, and documentation of pesantren activities. The results of this study that Fammi Bisyauqin is not merely a method of memorization maintenance, but also a means of spiritual strengthening, character building, and the actualization of hadith in pesantren life. These findings contribute new insights to the study of Living Hadith while enriching the discourse on Al-Qur'an learning methods in pesantren environments.